Disorders of the auditory system - Musiek, Frank E.; Shinn, Jennifer B.; Baran, Jane A.; Jones, Raleigh O. (San Diego c)
"The second edition of Disorders of the Auditory System reflects the combined efforts of renowned audiologists and otologists to provide to the reader with both the audiologic and medical aspects of auditory dysfunction associated with disorders of the peripheral and central auditory system. This book includes numerous insightful case studies covering both classic and unique clinical presentations that will provide informative reading for students and professionals in the fields of audiology, otology, and neurology"--
Structure and Function of the Auditory and Vestibular Systems -- Audiologic, Vestibular, and Radiologic Procedures -- Outer and Middle Ear Disorders -- Inner Ear Disorders -- Auditory Nerve Disorders -- Disorders of the Central Auditory Nervous System -- Tinnitus, Hyperacusis, and Auditory Hallucinations -- Hereditary and Congenital Hearing Loss.
Preceded by Disorders of the auditory system / Frank E. Musiek ... [et al.]. 2012.
Keywords: Audiology